Electronic arts : equity valuation - Cardoso, David Nobre Pinto (2019)
The following master thesis was elaborated by David Cardoso under the orientation of professor Dr. José Carlos Tudela Martins. The master thesis has as its main objective the valuation of Electronic Arts, a US based gaming/entertainment company. The Company was founded back in 1982 and since then has been operating in the mentioned sector namely by making game software for platforms such as personal computers, consoles and more recently smartphones. The Company has been enjoying success through its game franchises mainly in the sports category. The valuation process was made through two methods: Discounted Cash flows and Multiple relative valuation. In the DCF method, the Company’s future cash flows are estimated and discounted to present day. All those cash flows are then summed and yield the Enterprise value. The next procedure would be to add the cash in the balance sheet and subtract the Company’s debt to yield the Equity value. If the Equity value is divided by the number of shares outstanding which will result in the estimated value per share. In the Multiples relative valuation process, the financials of similar companies are used to make a comparison between what those companies are valued and what the Company should be valued. Finally, after doing both processes a final recommendation of buying and/or holding the Company.